Czy programy lojalnościowe są skuteczne? - Witek, Lucyna; Zatwarnicka-Madura, Beata (Are the Loyalty Programmes Efficient?, 2006)
The main aim of the article is to present and assess the Loyalty Programmes. The article shows: the phenomenon of customer loyalty, the core, tools and the process of building the Loyalty Programmes. The conditions of the Loyalty Programmes' success and the causes of failures were in the centre of our attention.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 369-376